Bacterial Profile and Antimicrobial Susceptibility Pattern in Septicemia Suspected Children and Available Treatment Options - Shaista Bakhat; Saman Nadeem; Ashfaq Hussain; Santosh Kumar Sidhwani; Hina Wasti; Yasmeen Taj; Faisal Faheem (Gandhara University, 2023)
OBJECTIVES Septicaemia (blood poisoning) is one of the chief sources of global morbidity and mortality in pediatric patients and presents with multidrug and extensive drug resistance. This study aims to detect the major causative agents, antimicrobial susceptibility patterns and associated factors of bacteraemia among pediatric patients. METHODOLOGY This retrospective cross-sectional study was done at National Medical Center, Karachi microbiology laboratory. Clinical specimens consist of blood. Blood samples were processed in BACTEC's automated blood culture system, and positive samples were sub-cultured on blood, Mac-Conkey. Final identification was done by API 20E and API 20NE (Biomerieux) and confirmed by MicroScan (Beckman coulter)®. The antimicrobial susceptibility was performed by using Bauer- Kirby disk diffusion method. RESULTS A total of 395 pediatric patients were taken in the study. Out of these patients, 226 (57.2 %) were female. The children with age 1-4 years were highly affected. Almost 50% were handled in emergency and transferred for admission. 36.2% of patients were exposed to intravenous devices. 89 (22.5%) patients had a history of prolonged use of antibiotics. Most patients with pneumonia presented with septicemia as a complication, and were detected by Klebsiella pneumonia (35.4%), Acinetobacter bauminii (25.3%) and Pseudomonas aeruginosa (20.3%).  CONCLUSION The study revealed that gram-negative organisms are the predominant causative organisms of septicaemia. Antibiotic resistance to Carbapenem is gradually increased in the case of Acinetobacter bauminii and Escherichia coli. These issues can be overcome by early detection of microorganisms and establishing antibiotic stewardship.